2020
DOI: 10.1111/avsc.12472
|View full text |Cite
|
Sign up to set email alerts
|

Savannah trees buffer herbaceous plant biomass against wild and domestic herbivores

Abstract: Questions Given the growing abundance and dominance of domestic herbivores in savannah ecosystems, can trees maintain plant herbaceous standing biomass under increasing herbivore pressure? Are there differences in the capacity of leguminous and non‐leguminous trees in sustaining understory herbaceous biomass? And finally, to what extent does plant community composition underneath trees modulate the effects of herbivore assemblage and abundance on herbaceous biomass? Location Pasturelands and protected areas al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…For instance, Belsky (1986a) found a sevenfold variation in regrowth in a clipping experiment on 14 common savanna grasses. High‐intensity, year‐round livestock grazing can act as strong selection pressure on savanna grassland species composition in wildlife grazed savannas, selecting for grassland species tolerant of higher biomass removal and generating distinct communities (Smith et al, 2020; Tegegn et al, 2011; Young et al, 2013). The consequence of changes in grass species composition caused by livestock grazing for plant productivity is less predictable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Belsky (1986a) found a sevenfold variation in regrowth in a clipping experiment on 14 common savanna grasses. High‐intensity, year‐round livestock grazing can act as strong selection pressure on savanna grassland species composition in wildlife grazed savannas, selecting for grassland species tolerant of higher biomass removal and generating distinct communities (Smith et al, 2020; Tegegn et al, 2011; Young et al, 2013). The consequence of changes in grass species composition caused by livestock grazing for plant productivity is less predictable.…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of changes in grass species composition caused by livestock grazing for plant productivity is less predictable. Livestock‐induced changes in savanna grassland composition variously increase, decrease, or have no effect on savanna plant productivity (Charles et al, 2017; Smith et al, 2020; Veblen et al, 2016). Although pastoral settlements may lead to greater grass dominance closer to settlements, changes in regrowth capacity will likely depend on species‐specific responses to disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…We approximated biomass at the onset of each productivity measurement using a calibrated disc‐pasture meter across a 30 × 30 m grid, and a 10 × 5 m grid at each site, matching the spatial resolution of Sentinel‐2 derived NDVI and field camera derived GCC respectively. Disc‐pasture meter measurements were averaged for each site before using a calibration equation ( R 2 = 0.83) specific to the Serengeti to convert the height (cm) of the disc into herbaceous biomass (g m −2 ) (unpublished data Smith et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall for the wet and dry season incubation periods were obtained from satellite-based daily rainfall estimates from NASA's Goddard Earth Sciences Data and Information Services Centre (Huffman 2017), based upon half-hourly measurements of cloud cover retrieved using multi-satellite microwave data at 10 × 10 km resolution. Previous work at the study sites showed significant positive correlation between these remote satellite based estimates of rainfall and soil moisture content (Smith et al 2020). From daily satellite rainfall estimates we calculated cumulative rainfall for each seasonal incubation period averaged at the site-scale.…”
Section: Soil Moisture and Rainfallmentioning
confidence: 99%